2004
DOI: 10.3349/ymj.2004.45.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Iron Supplementation in Experimental Hyperthyroidism: Effects on Oxidative Stress in Skeletal Muscle Tissue

Abstract: This study was designed to investigate the effects of iron supplementation on the parameters of oxidative stress in the skeletal muscle tissue of hyperthyroidism induced rats. Hyperthyroidism was found to cause an increase in thiobarbituric acid-reactive substances (TBARS) and copper zinc superoxide dismutase (Cu, Zn SOD) activity, but decreases in the glutathione-peroxidase (GSH Px) activity and glutathione (GSH). Iron supplementation caused an increase in TBARS and a decrease in GSH. Iron supplementation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 0 publications
3
14
1
5
Order By: Relevance
“…According IMAI et al (1991), increased TBARS associated with reduced NPTH values are a common figure in elevated oxidative stress situations. Iron supplementation can induce increases in TBARS and reduction in NPTH (SEYMEN et al, 2004). TROOST et al (2003), have reported that a single clinical dosis of iron sulphate can induce oxidative damage in healthy human subjects.…”
Section: Resultsmentioning
confidence: 99%
“…According IMAI et al (1991), increased TBARS associated with reduced NPTH values are a common figure in elevated oxidative stress situations. Iron supplementation can induce increases in TBARS and reduction in NPTH (SEYMEN et al, 2004). TROOST et al (2003), have reported that a single clinical dosis of iron sulphate can induce oxidative damage in healthy human subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Os resultados deste estudo mostraram uma diminuição na atividade das enzimas GPx e GR conforme observado no homogenato de músculo sóleo dos animais tratados com L-tiroxina em comparação com o grupo controle. Esses dados estão de acordo com Seymen et al 10 que relataram que o tratamento com a L-tiroxina induz a formação de ERO e provoca consequentemente uma inibição da atividade específica da GPx, enzima responsável pela conversão de H 2 O 2 em H 2 O. O tratamento dos animais com a CoQ10, demonstrou efeito protetor da substância, uma vez que a atividade das enzimas GPx e GR foram reestabelecidas para valores próximos ao grupo controle.…”
Section: A B Discussãounclassified
“…O tratamento com a L-tiroxina induziu o estresse oxidativo no homogenato do mús-culo sóleo de ratos como indicado pela diminuição nas concentrações de GSH e um aumento nas concentrações de GSSG no homogenato analisado. Essas alterações encontradas no ciclo redox da glutationa no presente estudo condizem com os encontrados por Seymen et al 10 no músculo esquelético e Mohamadin et al 22 no músculo cardíaco de ratos, os quais demonstraram diminuição significativa da GSH e aumento da GSSG em animais tratados com L-tiroxina. Em nosso estudo, o tratamento dos animais com a CoQ10, reestabeleceu as concentrações de GSH e GSSG, indicando efeito antioxidante da substância.…”
Section: A B a Bunclassified
See 2 more Smart Citations